Social Support Relations With Level Of Depression In The Elderly At Graha Marie Joseph Pontianak - Ariyanti, Sri; Rahmat, Rahmat (International Journal of Health Sciences, 2023)
Background:Elderly is someone who has reached the age of 60 years and over. As a person gets older, the elderly will experience a change either physical, psychosocial or social changes. One of the most prominent changes is the physical alteration, which is characterized by changes in biological functions that cannot be prevented from being present. Purpose: The purpose of this study was to determine the relationship between social support and the incidence of depression in the elderly at Graha Marie Joseph Pontianak. Methodology: The research method used Cross Sectional, sampling techniques using purposive sampling techniques with a sample of 24 respondents, Data analysis used is univariate analysis, bivariate using product moment tests, if the data is normally distributed and Spearman Rank if the data is not distributed normally. Results: It was found that the level of depression in the elderly at Graha Marie Joseph Pontianak was included in the category of mild depression, social support p = 0.048. Conclusion: There is a relationship between social support and the level of depression in the elderly.